The effects of convergence: Internationalisation and the changing distribution of net value added in large German firms - Anke Hassel; Jürgen Beyer (Max-Planck-Institut für Gesellschaftsforschung, 2001)
The paper examines whether and how the increasing internationalisation of firms impacts on the operation of a co-ordinated market economy. Following the tenets of agency theory it assumes that an emerging market for corporate control changes the monitoring mechanisms that oversee management. Since Anglo-American forms of monitoring are usually associated with a higher return for investors compared with Continental European firms, a change in the distribution of the net value added of firms is expected. Using financial data on 59 large German companies, the paper shows that the emerging convergence of German corporate governance practices to Anglo-American standards has had a weak, but significant, impact on the distribution of net value added. This is in contrast to the impact of the internationalisation of firms on product markets, which does not have an effect. Since the market for corporate control is, however, still underdeveloped in Germany, the main effects remain to be seen. – – Der Beitrag untersucht, ob und wie die Internationalisierung von Unternehmen das Institutionengefüge einer koordinierten Marktwirtschaft beeinflusst. Annahmen der Prinzipal-Agent-Theorie gehen davon aus, dass die Regulierung der Übernahmemärkte von Unternehmen die Ausschüttung der Nettowertschöpfung eines Unternehmens prägt. Wenn sich deutsche Unternehmen nun in zunehmenden Maße an das angloamerikanische Modell der Corporate Governance annähern, so kann man erwarten, dass ihr Ausschüttungsverhalten sich ebenso verändert. Anhand von Finanzdaten von 59 großen deutschen Unternehmen zeigt der Beitrag, dass die Konvergenz der deutschen Unternehmensführung zu angloamerikanische Praktiken einen schwachen aber signifikanten Einfluss auf die Verteilung der Nettowertschöpfung hat. Im Unterschied dazu finden sich keine Effekte der Internationalisierung von Unternehmen. Da der Übernahmemarkt in Deutschland jedoch noch immer stark unterwickelt ist, bleiben weitere Auswirkungen abzuwarten.
Keywords: 300; Corporate Governance; Dividende; Übernahme; Multinationales Unternehmen; Institutioneller Wandel; Prinzipal-Agent-Theorie; Deutschland